THE DEVELOPMENT OF COMPETITION IN THE ELECTRICITY MARKET (Промышленный Транспорт Казахстан, 2025)
The paper addresses the problem of development of competitive electricity markets inrelationships that were formed by the enactment of the law "On electric power industry",according to which it is prohibited to combine the activities of the transfer and sale andpurchase of electricity. The author considers types of violations of antitrust laws in the retail andwholesale electricity market, and draws conclusions on the further development of competitionin the electricity market.Various schemes of corporatization, privatization, consolidation with high-yielding typesof industries (e.g., aluminum production), expansion of the production chain by including theproduction of equipment for the power industry were proposed as the main reform ideas.Most of these projects were rejected due to infringement of the interests of privateshareholders or contrary to the interests of the company.